Autograft of tunica vaginalis as reinforcement of perineal herniorrhaphy in dog - A case report - de Faria, Barbra Gabriela Oliveira (2016)
ABSTRACT. Faria B.G.O., da Silva V.M., Muramoto C., Quessada A.M., Barbosa V.F., Silva E.A.C., Martins Filho E.F. & Costa Neto J.M. [Autograft of tunica vaginalis as reinforcement of perineal herniorrhaphy in dog - A case report.] Autoenxerto de túnica vaginal como reforço na herniorrafia perineal em cão - Relato de caso. Revista Brasileira de Medicina Veterinária, 38(Supl.1):1-8, 2016. Programa de Pós-Graduação Ciência Animal nos Trópicos, Universidade Federal da Bahia, Av. Ademar de Barros, 500, Ondina, Salvador, BA 40170-110, Brasil. E-mail: jmcn@ufba.br The orchiectomy, adjuvant surgery to the treatment of perineal hernia, provides a connective tissue that, like other biological membranes, has ideal characteristics for grafting. In this way, the use of the tunica vaginalis was described as a free auto graft to repair the pelvic diaphragm of a 12-year-old dog with unilateral reducible perineal hernia. The procedure consisted of two surgical times. Initially, a closed orchiectomy was performed. After excision of organs, the tunicae of both testicles were collected and prepared for a single double layer graft. In a second time, the hernia approach was performed, which was characterized by broad hernial ring, accompanied by slight muscular atrophy and the content of hernia consisted of bowel, bladder and prostate. After reduction of the content and muscle debridement, proceeded to the primary muscle synthesis by suture, which showed to be loss-making, just approaching the muscle edges, but with obvious tissue fragility. Then, the graft was attached to the muscles and covered by skin and intradermal sutures. The animal was followed by a period of 180 days after surgery by clinical and ultrasonographic analysis with any signs of complications or recurrence. It concludes that the tunica vaginalis autograft, obtained through prior orchiectomy, was a viable option for reinforcement of classical hernia repair of the pelvic diaphragm and can be used for the treatment of perineal hernia.